INFLUENCE OF PONGAMIA PINNATA, ANNONA SQUAMOSA AND LANTANA CAMARA WITH ALOE VERA AS A SYNERGIST ON F1 VIABILITY IN SPODOPTERA LITURA FABR. - DESHMUKHE, PRATIBHA V.; HOOLI, ASHOKA.; HOLIHOSUR, S.N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Crude aqueous extracts of Annona squamosa seeds, Pongamia pinnata leaves and a mixture of Lantana Camara leaf extract with Aloe vera inner leaf gel as a Synergist were tested against the fourth instar larvae of Spodoptera litura F. through topical application and oral administration through food. Their prolonged effect on the per cent egg hatchability and per cent FI larval mortality were recorded. The most significant ovicidal property was recorded for leaf application of P. pinnata extract (31.0 + 0.66 per cent hatchability at 40 per cent concentration, compared to the 60.66+0.66 per cent of control). The topical application at 40 per cent concentration of L. camara and A. vera synergistic mixture caused a high F1 neonate mortality (48.75 + 0.66 per cent, compared to the 5.97 - 0.66 per cent of control group). The topical application of A. squamosa seed extract however, did not exhibit any F1 neonate larvicidal effect.